Implementing Mobile Communication System Using FPGA - Goh, Seng How (Universiti Sains Malaysia, 2006)
Global System for Mobile Communication (GSM) is a digital cellular communication network that has been used by most of the countries around the world. GSM mobile phone is used since 1991, and uses variety of error detection and error correction techniques in communication system to improve the services’ quality. Thus, a research has been done on six parts of encoder and six parts of decoder in the GSM mobile phone communication system in order to produce chipsets using VHDL. The communication system is important for detecting errors, correcting and protecting speech data during transmission and receiving. Xilinx ISE 7.1i software in VHDL description is used as a tool in the research to enable each part of encoder and decoder to be modeled synthesized, simulated and implemented before downloaded on the FPGA device Spartan3 XC3S1500E-FG676. Furthermore, the FPGA device is capable to be programmed many times using different design. In this research, the simulation result for each part of encoder and decoder shows that 260 until 592 speech bits are gained in 20 ms based on the GSM standard. The download result is also similar to the simulation result for each part of encoder and decoder. After the download process, the chipsets of GSM mobile phone communication system are produced.